Pedagogical basis of interdisciplinary communication in the educational process - Norkobilova Rayxona Davlatovna (International Journal on Orange Technologies, 2020)
The article describes the content of the development of creativity in the formation of ecological concepts in primary school science lessons, the combination of teaching methods, forms and means, improving their ecological culture through the organization of lessons, the formation of feelings of natural beauty, feelings of conservation and personal life.